Molecular organization and recognition properties of amphiphilic cyclodextrins - Hoyos, Maria Rita Micaela (2009)
The continuing challenge of using cyclodextrins (CDs) for solubilization and drug targeting has led to the preparation of a wide variety of chemically modified derivatives in order to improve the properties of these host molecules. A possible approach for pharmaceutical applications would be to combine the recognition specificity of CDs with the transport properties of organized structures such as vesicles, liposomes, or micelles. Amphiphilic CDs can be admixed to phospholipid monolayers and to liposomes, and they can be dispersed into nanospheres showing promising properties for drug encapsulation. Monoacylated derivatives of ß-CD, Mod-CD (Cn), were synthesized in our laboratory from the reaction of alkenyl succinic anhydride with β-CD. We found that the compound with 10 carbon atoms in the alkenyl chain, Mod-CD (C10), can be incorporated into inverted micelles. We studied their properties in solution and at the air-water interface. In solution they have very low critical micellar concentration, and in the aggregates there are two recognition sites: one is the cavity of the CD and the other is formed by the hydrophobic tails. The alkenyl chain interacts with the cavity, but this is not an obstacle for the association with external guests such as 1-amino adamantane, Phenolphthalein, or Prodan. Mod-CD (Cn) with n equal to 10, 14, and 16 (n indicates the number of carbons in the alkenyl chain), form stable monolayers at the air-water interface and they adopt an organization very different from those found for persubstituted CDs. The differences are attributed to the higher conformational flexibility of these compounds, which allows the organization of the CD units with the cavity perpendicular to the interface.